Community-engaged research as a pathway to oral health equity: insights from a Texas initiative - Price, Cody; Williams, Blair; Jacks, Andrea Mayo; Sanghavi, Ankit (Frontiers in Public Health, 2025)
Solutions to advance oral health equity require a deeper understanding only achieved though partnership with the communities deeply impacted by barriers to care. While numerous studies and dental public health reports published over the years demonstrate a need for oral health equity, there is a paucity of literature regarding community engagement as a pathway to advancing oral health equity. As a human-centered design approach, Community-Engaged Research (CER) provides opportunities to engage communities as research partners, while developing trust and capacity for sustainable collaboration and participatory systems thinking. Building on literature and our experiences from leading a community-engaged oral health equity project in Texas, this perspective article offers actionable concepts of trust, time, and co-design to encourage the use of community-engaged practices that assess and address complex factors that impact oral health.